(untitled) (International Journal of Food and Nutritional Sciences, 2024)
A descriptive study conducted to assess the prevalence of anaemia among the college students in the selected institutions at Dindigul district Tamilnadu. Totally 650 samples were recruited by using convenience sampling method. Digital hemoglobinometer used to check the hemoglobin level and self devised questionnaire used to collect the selected demo graphical variables. Statistical analysis revealed the majority of the college students are having mild anaemia,17.6% of students were having moderate anaemia, 12.1% were not having anaemia and only 4.6% were having severe anaemia. Also the demographic variables such as age, sex, dietary pattern, place of residence and de-worming significant association with the level of Hemoglobin at 0.05 level. But there was no significant association with the demographic variable Institution where they were studying. This study concluded that our young generation affected with anaemia in spite of vigorous and intensive anaemia control programs. So still we need to execute the tremendous measures to control and treat the anaemia. Also its imperative to execute the modifications in their dietary pattern and life style as a whole in order to brig out the healthy and productive younger generation.